Immediate Bacille Calmette-Guérin Vaccination to Neonates Requiring Perinatal Treatment at the Maternity Ward in Guinea-Bissau: A Randomized Controlled Trial. (24th April 2021) - Schaltz-Buchholzer, Frederik; Aaby, Peter; Monteiro, Ivan; Camala, Luis; Faurholt Simonsen, Simone; Nørtoft Frankel, Hannah; Lindberg Larsen, Kristina; Golding, Christian N; Kollmann, Tobias R; Amenyogbe, Nelly; Stabell Benn, Christine; Bjerregaard-Andersen, Morten
Abstract: Background: Randomized controlled trials (RCTs) indicate that bacille Calmette-Guérin (BCG) vaccination provides broad beneficial "nonspecific" protection against infections. We investigated the effect on in-hospital mortality of providing BCG immediately upon admission to a neonatal intensive care unit (NICU), rather than BCG-at-discharge. The pretrial NICU mortality was 13% and we hypothesized that BCG would reduce mortality by 40%. Methods: Parallel-group, open-label RCT was initiated in 2013 in Guinea-Bissau. Neonatal intensive care unit-admitted neonates were randomized 1:1 to BCG + oral polio vaccine (OPV) immediately (intervention) versus BCG + OPV at hospital discharge (control; usual practice). The trial was discontinued due to decreasing in-hospital mortality and major NICU restructuring. We assessed overall and disease-specific mortality by randomization allocation in cox proportional hazards models providing mortality rate ratios (MRRs). Results: We recruited 3353 neonates, and the overall mortality was 3.1% (52 of 1676) for BCG-vaccinated neonates versus 3.3% (55 of 1677) for controls (MRR = 0.94; 0.64–1.36). For noninfectious causes of death, the MRR was 1.20 (0.70–2.07), and there tended to be fewer deaths from infections in the BCG group (N = 14) than among controls (N = 21) (MRR = 0.65; 0.33–1.28). Conclusions: Providing BCG + OPV to frail neonates was safe and might protect against fatal infection in the immediate newborn period. Deaths due to prematurity and perinatal complications were unaffected by BCG. Abstract : In a randomized controlled trial from Guinea-Bissau, providing BCG immediately compared with BCG-at-discharge to neonates admitted to the neonatal intensive care unit did not affect overall in-hospital mortality significantly, but it tended to reduce deaths from infectious diseases.